A Practical Primer on Prion Pathology. Issue 5 (28th March 2018) - Appleby, Brian S; Rhoads, Daniel D; Mente, Karin; Cohen, Mark L
Abstract: Prion diseases comprise a group of transmissible degenerative encephalopathies resulting from propagation of a misfolded cellular protein of uncertain function. As is generally the case with rare diseases, lack of institutional experience compromises individual familiarity with the varying, and apparently protean, manifestations of prion diseases, both clinically and pathologically. Coupled with the documented transmissibility of these diseases both within and between species, the Centers for Disease Control and Prevention (CDC) has established the National Prion Disease Pathology Surveillance Center to both aid with diagnosis of prion disease and to survey the United States for evidence of zoonotic transmission. We have assembled this primer with the hope that our accumulated experience will enable the neuropathological community to help the CDC "save lives and protect people."